2000
DOI: 10.1002/1097-0290(20001205)70:5<507::aid-bit5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde-mediated aggregation of protein antigens: Comparison of untreated and formalinized model antigens

Abstract: A formaldehyde‐mediated aggregation pathway (FMAP) is suggested as being primarily responsible for the aggregation of lyophilized tetanus toxoid (TT; a formalinized antigen) in the presence of moisture. The general occurrence of the FMAP was examined by using bovine serum albumin (BSA) and ribonuclease A (RNase) as model antigens; both protein antigens were formalinized according to a method commonly used to detoxify bacterial toxins. To clearly delineate the FMAP from other aggregation mechanisms, the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Furthermore, RNase A is a single chain polypeptide containing 4 disulfide bridges [44]. Previous gel electrophoresis study has showed that formaldehyde treatment of RNase A leads to a rapid formation of protein cross-links [45], [46]. Thus, RNase A was used as a positive control in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RNase A is a single chain polypeptide containing 4 disulfide bridges [44]. Previous gel electrophoresis study has showed that formaldehyde treatment of RNase A leads to a rapid formation of protein cross-links [45], [46]. Thus, RNase A was used as a positive control in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…35 Although peptide cleavage rates have not been directly related to PLGA hydrolysis rates, the hydrolysis of Asp-Pro bonds in bovine serum albumin (BSA) was prevented by switching from a 50/50 PLGA to PLA-PEG. 44 Because hydrolysis of the BSA AspPro bond is acid catalyzed, 45 degradation of this protein was mediated by encapsulation in polymer system that did not allow for the accumulation of acidic monomers and oligomers.…”
Section: Amide Bond Hydrolysismentioning
confidence: 99%
“…The main reason may be that the NH or NH 2 groups in L-histidine molecule can react with formaldehyde, 33,34 and their reaction is described by equation (10).…”
Section: Mechanism Of Formaldehyde Releasementioning
confidence: 99%